2015
DOI: 10.1021/acs.chemmater.5b03506
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Programmed Nanofabrication: Effect of Organophosphite Precursor Reactivity on the Evolution of Nickel and Nickel Phosphide Nanocrystals

Abstract: A better understanding of the chemistry of molecular precursors is useful in achieving more predictable and reproducible nanocrystal preparations. Recently, an efficient approach was introduced that consists of finetuning the chemical reactivity of the synthetic molecular precursors used, while keeping all other reaction conditions constant. Using nickel phosphides as a research platform, we have studied how the chemical structure and reactivity of a family of commercially available organophosphite precursors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 124 publications
2
42
0
Order By: Relevance
“…To the best of our knowledge, in only one previous report the reactivity of TPOP was studied among that of several other candidates as a source of phosphorous for the synthesis of nickel phosphide. 63 Surprisingly, in spite of the promising results obtained in this previous work, no follow up report has considered TPOP as phosphorous precursor. Apart from this, TPOP has been rarely used as a stabilizer in the synthesis of Au 64 and CuInS 2 65, 66 NPs.…”
mentioning
confidence: 81%
“…To the best of our knowledge, in only one previous report the reactivity of TPOP was studied among that of several other candidates as a source of phosphorous for the synthesis of nickel phosphide. 63 Surprisingly, in spite of the promising results obtained in this previous work, no follow up report has considered TPOP as phosphorous precursor. Apart from this, TPOP has been rarely used as a stabilizer in the synthesis of Au 64 and CuInS 2 65, 66 NPs.…”
mentioning
confidence: 81%
“…Solution phase LiZnP was originally prepared by injecting diethyl zinc into a solution containing lithium hydride in trioctylphosphine at 250 °C (nucleation temperature), followed by subsequent heating to 330 °C (growth temperature). The reaction proceeds through a mechanism similar to some binary metal phosphides . Specifically, metallic Zn seeds are formed upon injection of the zinc precursor, followed by intercalation of Li and P. This synthesis is also extremely flexible, with multiple Li, Zn, and P precursors able to be used successfully.…”
Section: Lithium‐based Nowotny–juza Phasesmentioning
confidence: 99%
“…[12] Solution phase LiZnP was originally prepared by injecting diethyl zinc into as olution containing lithium hydride in trioctylphosphine at 250 8C( nucleation temperature), followed by subsequenth eatingt o3 30 8C( growth temperature).T he reaction proceeds through am echanism similart os omeb inary metal phosphides. [25][26][27][28][29][30][31][32][33] Specifically,m etallicZ ns eeds are formed upon injection of the zinc precursor,f ollowed by intercalationo fL ia nd P. This synthesis is also extremelyf lexible, with multiple Li, Zn, and Pp recursors able to be used successfully.F or instance, the homogeneity and overall controlo ft he reactionc an be increased with organolithium reagents such as n-butyllithium or lithium diisopropylamide. These reagents undergo b-hydride elimination to yield LiH in situ when heated past % 125 8C.…”
Section: Liznpmentioning
confidence: 99%
“…35 Initially thought to be a semiconductor, electronic structure calculations revealed that bulk Ni 2 P is actually metallic. 36,37,38 Interestingly, their resemblance to noble metals goes well beyond HER, as first row transition metal phosphides are also active catalysts in hydrotreating (HDX, X = S or hydrodesulfurization, 39,40,41,42 O or hydrodeoxygenation 43,44,45 , and N or hydrodenitrogenation 46,47 ), alkyne hydrogenation, 48,49,50,51 and hydrodearomatization reactions. 52 The ability of Ni 2 P and other Earth-abundant, binary metal phosphides to readily and reversibly adsorb hydrogen (H 2 ), perform a wide range of hydrogenation-like reactions, and achieve high product selectivities strongly suggest that they could also catalyze the hydrogenation of other, typically more challenging reactants, such as nitrate (NO 3 -).…”
Section: Introductionmentioning
confidence: 99%